Edukasi literasi terhadap warga binaan pemasyarakatan membaca dan memahami kitab suci - Hutahaean, Hasahatan; Sefendi, Sefendi; Sinaga, Luhut (University of Islam Malang, 2021)
This community service activity is aimed at the community assisted by the prison in Binjai Class II Lapas, Sumut. The situation that encourages the implementation of this activity is the large number of assisted residents who spend their free time just sitting and chatting. On the other hand, they are people who need guidance, be it moral, spiritual, and also training related to the needs of the community after going through the prison process. The method of activity is community development in prison. Activities carried out with training and group exercises. The material provided was then trained in each group. This community service activity takes a model of how to understand the text of the Bible in Christianity which is called Bible Digging (BGA). The BGA method is very simple and in its simplicity, it is believed to encourage Christians to live better lives in God and to pray diligently. The BGA training was finally able to motivate the assisted residents to read the Bible more actively and committed. Therefore, it is hoped that similar training can be adopted for Lapas or other communities to provide a better sense of well-being.